2012
DOI: 10.2298/fil1206189l
|View full text |Cite
|
Sign up to set email alerts
|

Sharp bounds on Zagreb indices of cacti with k pendant vertices

Abstract: For a (molecular) graph, the first Zagreb index M 1 is equal to the sum of squares of its vertex degrees, and the second Zagreb index M 2 is equal to the sum of products of degrees of pairs of adjacent vertices. A connected graph G is a cactus if any two of its cycles have at most one common vertex. In this paper, we investigate the first and the second Zagreb indices of cacti with k pendant vertices. We determine sharp bounds for M 1-, M 2-values of n-vertex cacti with k pendant vertices. As a consequence, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…We quote here only some most recent works of this kind, [59][60][61][62][63][64][65] in which references to earlier studies can be found. Numerous papers on Zagreb indices are appearing also in mathematical journals; see the recent articles [66][67][68][69][70] and the references cited therein.…”
Section: Zagreb Indicesmentioning
confidence: 99%
“…We quote here only some most recent works of this kind, [59][60][61][62][63][64][65] in which references to earlier studies can be found. Numerous papers on Zagreb indices are appearing also in mathematical journals; see the recent articles [66][67][68][69][70] and the references cited therein.…”
Section: Zagreb Indicesmentioning
confidence: 99%
“…As it is well known in graph theory, topological indices are very popular characterization methods for simple graphs. Therefore one may adapt some special indices (for example, Zagreb indices ( [18,29,36])) or irregularity index ( [4]) to the our new graph defined in this paper. On the other hand, as another future project, since the main idea in the paper [13] was to defined a new graph over a special algebraic structure, namely finite monogenic monoids, and since our main goal in here is quite similar with that paper (just by replacing monoids with groups), one may also study some special graph products (for instance, lexicographic, tensor, cartesian etc.)…”
Section: Perfectness Property Of γ(G)mentioning
confidence: 99%
“…In this paper we obtain the explicit formulae for hyper-Zagreb index of a graph for four operations in F-sums. For the computational techniques we refer [8,11,12,13].…”
Section: Introductionmentioning
confidence: 99%